Flora and Fauna of the Civil War : An Environmental Reference Guide - Ouchley, Kelby, 1951- (Book collections on Project MUSE., 2010)
During the Civil War, humans impacted plants and animals on an unprecedented scale as soldiers on both sides waged the most environmentally destructive war ever on American soil. Refugees and armies alike tramped across the landscape foraging for food, shelter, and fuel. Wild plants and animals formed barriers for armies and carried disease, yet also provided medicine and raw materials necessary to implement war, greatly influencing the day-to-day life of soldiers and civilians alike. Of the thousands of books written about the Civil War, few mention the environment, and none address the topic.